Lonicera japonica Thunb.: Ethnopharmacology, phytochemistry and pharmacology of an important traditional Chinese medicine - Shang, Xiaofei (J Ethnopharmacol, 2011)
ETHNOPHARMACOLOGICAL RELEVANCE: Lonicera japonica Thunb. (Caprifoliaceae), a widely used traditional Chinese medicine, was known as Jin Yin Hua (Chinese: [Image: see text]), Ren Dong and Japanese honeysuckle. It was taken to treat the exopathogenic wind-heat, epidemic febrile diseases, sores, carbuncles and some infectious diseases. At the same time, Lonicera japonica could be used as healthy food, cosmetics, ornamental groundcover, and so on. AIM OF THE REVIEW: The present paper reviewed the ethnopharmacology, the biological activities, toxicology and phytochemistry of Lonicera japonica. MATERIALS AND METHODS: Information on Lonicera japonica was gathered via the Internet (using Google Scholar, Baidu Scholar, Elsevier, ACS, Medline Plus, CNKI and Web of Science) and libraries. Additionally, information also was obtained from some local books and brilliant scholars on ethnopharmacology. RESULTS: More than 140 chemical compounds have been isolated, and the main compositions are essential oils, organic acids and flavones, etc. Lonicera japonica and its active principles possess wide pharmacological actions, such as anti-inflammatory, antibacterial, antiviral, antioxidative and hepatoprotective activities. CONCLUSIONS: As an important traditional Chinese medicine, further studies on Lonicera japonica can lead to the development of new drugs and therapeutics for various diseases, and how to utilize it better should be paid more attentions.